If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2 + -1x) = -8 + 6x (2 * -2 + -1x * -2) = -8 + 6x (-4 + 2x) = -8 + 6x Solving -4 + 2x = -8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + 2x + -6x = -8 + 6x + -6x Combine like terms: 2x + -6x = -4x -4 + -4x = -8 + 6x + -6x Combine like terms: 6x + -6x = 0 -4 + -4x = -8 + 0 -4 + -4x = -8 Add '4' to each side of the equation. -4 + 4 + -4x = -8 + 4 Combine like terms: -4 + 4 = 0 0 + -4x = -8 + 4 -4x = -8 + 4 Combine like terms: -8 + 4 = -4 -4x = -4 Divide each side by '-4'. x = 1 Simplifying x = 1
| 11+2n=9 | | -7(1x-6)=-14 | | 57=5x-3 | | -3(5m+4)-3(m-7)= | | y-12=89 | | 5x^2+11xy+2y^2=0 | | mx=-nx+p | | 9x-15=9(x-13) | | 38=8+6(y+2) | | 136=-17b | | -27.083x-11.246-16.819= | | f(x)=-27.083x-11.246-16.819 | | -2+y=4x+9 | | k^2+2k-75=5 | | 13-6a+2a=5-6a | | 28=k/5 | | 4x^2-0.2x+0.01=0 | | 8[m+5]=16 | | x+5+1=x | | a^2+2a-17=7 | | 16p+16q+p-4q-5p= | | Y=8mx-9b | | 11x+8-4x=-9x-10+x | | x^2+20x-15=6 | | 4(d-2)+5= | | 5-3(1-x)=-16 | | 7(4x+8)-6=106 | | f(2.885)=-5.89+6.357 | | 6x^2+7=13 | | 5y+3=2y+20 | | 2ln(x)+ln(6x+7)=ln(9x-2) | | 3(2d-1)-2d= |